A Realistic Theory of Law (Book Review) - Kabir, Syahrul Fauzul (Brawijaya Law Journal, 2019)
Despite the law has been developing through the span of the history of human civilization, law has been formulated by legal thinkers, theologians, philosophers; constructed with various pretexts and objectives: for legal certainty, utility, justice and order; used to regulate social life in various forms and dimensions: customary law, religious law, state law, international law, the formulation of legal theory, to date, is still an academic debate.            It is Brian Z. Tamanaha, a professor of law from America, who also entered the theoretical debate's arena through his academic works. In the contemporary legal discourse, Tamanaha is quite popular among academics and legal activists. Tamanaha is known globally due to his famous works, such as "A General Jurisprudence of Law and Society (2001)", which received Herbert Jacob Bookrize awards, and "On the Rule of Law: History, Politics and Theory (2004)", which have been translated into 6 languages. His position as an important legal thinker in the 21st century gained his legitimacy in 2013. Through a poll, which involved 300 deans and professors from various universities in America, Tamanaha was regarded as the most influential legal educator.            Tamanaha is often cited by many legal thinkers in Indonesia, among others, by Satjipto Rahardjo, especially regarding Tamanaha's concept known as the mirror thesis. Through this notion, Tamanaha argues that law is only a reflection of certain ideas, values, cultures and traditions of society. Because law is always particular, referring to certain societies in particular temporal circumstances, then, legal transplantation from and/or to other communities is not realistic if not impossible. His thinking, inevitably influenced by the Anglo Saxon legal tradition that grows and practiced in his homeland America, which tends to be more dynamic and reliant on jurisprudence.            On April 24, 2017, Cambridge University Press published Tamanaha's latest book entitled "A Realistic Theory of Law". Examining the composition of the book's contents: contained a debate regarding law's definition, the schools of law, genealogy of law, while questioning the truth and the universality of law, presumably implying that Tamanaha was constructing his own legal theory as reflected in the book's title ("Theory of Law"). Based on this description, the author is interested in exploring Tamanaha's legal thinking; outlining his opinions on the essence of law, through his newest book which numbered 202 pages.            The first part of the book discusses three most prominent theories or legal philosophies (Jurisprudence) in various legal discourses: The School of analytical law (legal positivism), philosophical/ethical (natural law) and historical (historical schools). Throughout history, from medieval times to renaissance, the conflict between these schools of jurisprudence was reviewed through its exponents thinkers. Then, Tamanaha entered the arena using the socio-legal framework's, in order to overcome the gap between these schools of law.            In the second chapter, Tamanaha reviews the classical debate on law, namely questioning the legal definition in a sub-title "what is law?". The three branch of jurisprudence, as mentioned previously, are joined to disscuss the problematic definition of law. Then, Tamanaha not only criticizes the proposed law definitions, elucidating the shortcomings and failures of established legal definitions, but also tries to reconstruct it.            Chapter three contains description with regard to the claim of law's universality. Here, Tamanaha critically discusses the basic assumptions of law and the implicit legal features from the mainstream law's perspective. Differentiation between laws as social construction, which varies in each society due to the variety of cultures, environments, etc. (a posteriori), is faced diametrically with the identification of idealized laws, which can be applied universally (a priori). The discussion raises a debate on the universality of the nature of law (universal truth); identification of legal characteristics, and the possibility of its implementation in a universal way.            Tamanaha, in the fourth part, uses genealogical approach of law; tracing the relationship between law and non-law elements, such as: economic, social, political, environmental, technological, cultural, in a diverse historical contexts. On the one hand, Tamanaha is concerned with historical developments related to legal structures; how law is formed and what elements have influenced law, by citing historians, sociologists, anthropologists viewpoint, etc. On the other hand, Tamanaha scrutinize analytical law's arguments, especially the positivist school; suing the basic assumptions of state law which has been hegemonic as the standard, in determining entity referred to as law.            The fifth part of the book is entitled "Law in the Age of Organizations". Tamanaha begins this chapter by claiming that legal theories have failed in calculating fundamental changes in law and society, which are marked by the rise of formal legal instruments. Tamanaha claims that his legal theory is more suited to modernity. Tamanaha distinguishes between law as the core regulation for social interaction and the use of law by the state. Furthermore Tamanaha explained how the interaction between the two categories affected the creation of legal structures in the community.            Before arriving at conclusions, Tamanaha ends the discussion in this book through the last part entitled "What is International Law". Tamanaha claims that international legal theories have a problem due to the confusions of concepts and ideological views constructed in international legal discourse. Conceptual barriers trigerred by Jeremy Bentham's theoretical paradigm in which he created a gap between domestic law and international law as separate entities. While ideological barriers stem from normative tendencies or commitments among international law experts in establishing a universal legal system; thus creating a false vision related to the locus of international law and its relation with national law. By outlining these confusion, Tamanaha believes he can provide a more comprehensive understanding of international law.